(untitled) (Journal of Scientific Research, 2011)
Microwave promoted diammonium hydrogen phosphate, (NH4)2HPO4, catalyzed three-component Biginelli reaction between an aldehyde, a 1,3-dicarbonyl compound and urea or thiourea under solvent-free conditions afforded the corresponding dihydropyrimidinones and quinazolinones in high yields. The synthesized compounds have been screened for their antimicrobial activity against Pseudomonas aeruginosa, Staphylococcus aureus, Vibrio choloriae, Shigella dysenteriae, Salmonella typhi bacteria and Aspargilllus flavus, Saccharomyces cerevisiae and Candida albicans fungi respectively. Some of the synthesized compounds exhibited pronounced antimicrobial activities. Keywords: Multicomponent reactions; Dihydropyrimidinone; Microwave irradiation; Antimicrobial activity. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i1.8688 J. Sci. Res. 4 (1), 143-153 (2012)